Ancora da capo: Об «Элегии» Александра Введенского [Ancora da capo: On Alexander Vvedensky’s “Elegy”] - Ustinov, Andrei (Slavica Revalensia, 2026)
This article is dedicated to Alexander Vvedensky’s most famous poem, “Elegy,” which is examined from a new perspective, i.e. in the context of the formation of the OBERIU poetic platform and in comparison with the poem that can be considered its predecessor, “Elegy” by Igor Bakhterev.